2021
DOI: 10.1186/s43088-021-00119-6
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using Omani pomegranate peel extract and two polyphenolic natural products: characterization and comparison of their antioxidant, antibacterial, and cytotoxic activities

Abstract: Background Green synthesis of silver nanoparticles (AgNPs) has gained popularity due to the economical and eco-friendly approach associated with it. The aim of the study was to biosynthesize silver nanoparticles using pomegranate peel extract (PPE), quercetin (Q), and gallic acid (GA) and to evaluate their antioxidant, antimicrobial, and cytotoxic activities. Results A sharp color change from yellow to brown, appearance of a peak in a UV spectrum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…1b). This result is consistent with the plasmon resonance peak for the silver which has been reported in the range of 391-460 nm 20,35 . According to Fig.…”
Section: Characterization Of Biosynthesized Agnpssupporting
confidence: 92%
“…1b). This result is consistent with the plasmon resonance peak for the silver which has been reported in the range of 391-460 nm 20,35 . According to Fig.…”
Section: Characterization Of Biosynthesized Agnpssupporting
confidence: 92%
“…The results depicted the spherical agglomerated particles with the range of 50-100 nm in a micrograph of AgNPs and the scale was used at range of 1-10 μm (Figs 5 and 6). The results of the present work are parallel with previous studies that reported the spherical AgNPs synthesis by pomegranate peel extract [29], seed extract of dates [46] and extract of cheese weed mallow [47].…”
Section: Plos Onesupporting
confidence: 91%
“…Scanning electron microscopy (SEM). Morphology of AgNPs (Shape and size of powdered Ag nanoparticles) was measured by SEM (JSM-5910, JEOL Japan) [29].…”
Section: Characterization Of Agnpsmentioning
confidence: 99%
“…1a and b. The maximum absorbance at wavelength 431.19 nm confirmed the formation of AgNPs because plasmon resonance peak in the range of 391-460 nm has been reported as the absorbance of silver [32].…”
Section: Visual Observation and Uv-visible Spectroscopymentioning
confidence: 75%